2016
DOI: 10.1002/ece3.2500
|View full text |Cite
|
Sign up to set email alerts
|

Development of methane conversion factor models for Zebu beef cattle fed low‐quality crop residues and by‐products in tropical regions

Abstract: The enteric methane conversion factor (Y m) is an important country‐specific value for the provision of precise enteric methane emissions inventory reports. The objectives of this meta‐analysis were to develop and evaluate the empirical Y m models for the national level and the farm level for tropical developing countries according to the IPCC's categorization. We used datasets derived from 18 in vivo feeding experiments from 1999 to 2015 of Zebu beef cattle breeds fed low‐quality crop residues and by‐products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…15% of gross energy (Johnson et al, 2007;Patra and Lalhriatpuii, 2016). In the present study, energy loss as CH4 (% GE) ranged between 8.8 and 9.6%; these values are comparable to those reported for beef cattle fed low-quality rations in tropical regions (Ym between 7-9%; Kaewpila andSommart, 2016, Molina et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…15% of gross energy (Johnson et al, 2007;Patra and Lalhriatpuii, 2016). In the present study, energy loss as CH4 (% GE) ranged between 8.8 and 9.6%; these values are comparable to those reported for beef cattle fed low-quality rations in tropical regions (Ym between 7-9%; Kaewpila andSommart, 2016, Molina et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…The loss of dietary gross energy as CH 4 with the control diet was higher than for the diet with alternate supplementation (8.1 vs 7.6% GE). These values are within the range reported by authors such as Kennedy and Charmley, (2012), Richmond et al (2015), Kaewpila and Sommart, (2016) and Molina et al (2016) for cattle fed improved or native corrected by weight gain was reduced when animals were fed E. cyclocarpum mixed with G. sepium. These findings are consistent with those of Warner et al (2017) who stated that reducing the nutritional quality increased CH 4 emission intensity (g CH 4 /kg of fat-and protein-corrected milk) by 28%.…”
Section: Discussionsupporting
confidence: 89%
“…However, another trial feeding tropical forages under ad libitum conditions reported a greater range of Y m of 5•0-7•2 % (35) , with the highest values occurring when cattle were fed very low-quality grass, at what would have been effectively sub-maintenance requirements. Kaewpila & Sommart (36) calculated (from earlier studies) a Y m of 8•2 % for B. indicus cattle fed low-quality foragebut a limitation of this study is that it does not seek to separate the possible influences of feeding levels from feed quality. While each of the studies detailed above, as well as the one reported here, has been conducted using cattle of predominantly B. indicus origins, it could be tempting to attribute the higher Y m values to breed effects.…”
Section: Discussionmentioning
confidence: 93%